The effect of non-AGP feed on blood cholesterol and profile of meat fat of broiler chickens reared in different regions - Tugiyanti, Elly; Susanti, Emmy (Faculty of Animal Science, Universitas Brawijaya, 2021)
This study aimed to determine the levels of blood cholesterol, meat fat and cholesterol, and fatty acids of broiler chickens fed non-AGP feed in three different regions. The material used consisted of 45 broilers from 3,000-10,000 broiler breeders and during maintenance they were not given any antibiotics at all. The research method used is a survey method. The data obtained were then analyzed by One Way ANOVA using the General Linear Model with regional differentiating factors, namely Banyumas, Cilacap, and Purbalingga. The variables observed included total blood cholesterol levels, blood low-density lipoprotein (LDL), blood high-density lipoprotein (HDL), blood triglycerides, meat cholesterol, and total fat of broiler chicken in Banyumas, Purbalingga, and Cilacap areas. The results showed that the use of non-AGP feed in broilers raised in three different areas resulted in total cholesterol, HDL, LDL, triglycerides, fats, and fatty acids which were not significantly different (P> 0.05), but produced meat cholesterol. different (P <0.05). It can be concluded that the non-AGP feed given to broilers in three different regions resulted in relatively the same blood cholesterol, fat, and meat fatty acid profile, but caused the meat cholesterol levels in the three regions to be different.